High-performance fiber polymer material and spinning preparation method thereof
The described method enhances fiber polymer material performance by using nano-materials in core and shell layers with alternating curing, addressing uniformity and durability issues, resulting in improved mechanical and chemical resistance for broader applications.
Patent Information
- Application Number
- CN202411251346.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-07
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing spinning preparation methods for fiber polymer materials lack optimization of processing performance, mechanical properties, heat resistance, chemical corrosion resistance, and uniformity of raw material mixing, leading to limitations in application fields and material durability.
A method involving the preparation of core and shell layer solutions with specific nano-materials, followed by alternating thermal and photocuring, including steps like ultrasonic and vacuum degassing to ensure uniformity and purity, and a multi-step curing process to enhance mechanical and chemical properties.
The method results in a high-performance fiber polymer material with improved tensile strength, modulus, heat resistance, chemical corrosion resistance, and uniformity, expanding its application scope to extreme environments and reducing production defects.
Smart Images

Figure BDA0005032408680000191 
Figure BDA0005032408680000201
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spinning preparation, in particular to a high-performance fiber polymer material and a spinning preparation method thereof. Background Art
[0002] The fibers prepared by the traditional spinning preparation method have a simple structure and a single curing method. The spinning preparation method of the present application prepares a fiber polymer material with a core layer structure, and alternately performs thermal curing and photocuring on the prepared fiber polymer material. The core layer structure enables the fiber polymer material to have higher strength and modulus while maintaining its light weight. By alternating between thermal curing and photocuring, the performance of the fiber can be flexibly adjusted while avoiding the limitations that may be caused by a single curing method. The processing performance of the fiber polymer material can be optimized, and the mechanical properties of the fiber polymer material can be improved.
[0003] The defects of the existing spinning preparation method are:
[0004] 1. Patent document CN113882024B discloses a method for preparing starch nanofibers by electrospinning. The document mainly considers how to improve the safety of starch nanofibers so that they can be used in the fields of food, medicine and cosmetics, but does not consider how to optimize the processing performance of fiber polymer materials and improve the mechanical properties of fiber polymer materials;
[0005] 2. Patent document CN100491612C discloses a seaweed fiber gel spinning preparation process. This document mainly considers how to overcome the problems of low spinning concentration, low spinning capacity and low strength of seaweed fibers, but does not consider how to improve the heat resistance and chemical corrosion resistance of fiber polymer materials, thereby broadening the application field of fiber polymer materials;
[0006] 3. Patent document CN110644071B discloses a method for preparing photoluminescent fibers by centrifugal spinning. The document mainly considers how to achieve the photoluminescent properties of the fibers while ensuring continuous collection of the fibers, but does not consider how to mix the raw materials evenly, improve the purity of the core layer solution and the shell layer solution, and the quality of the prepared fiber polymer material;
[0007] 4. Patent document CN111910272B discloses a method for preparing phenolic fibers by melt-blown spinning. The document mainly considers the problem of how to determine the optimal process parameters for preparing phenolic fibers by melt-blown spinning, but does not consider how to avoid the presence of bubbles in the preparation process, which leads to the formation of voids and defects in the fiber polymer material, thereby reducing the mechanical properties and durability of the fiber polymer material. Summary of the invention
[0008] The object of the present invention is to provide a high-performance fiber polymer material and a spinning preparation technology thereof to solve the problems raised in the above background technology.
[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a spinning preparation method of a high-performance fiber polymer material, the spinning preparation method of the high-performance fiber polymer material is as follows:
[0010] Step S1, preparing a polystyrene solution, a nano-silicon dioxide suspension, and a chitin and chitosan mixed acetic acid solution;
[0011] Step S2, preparing a polydopamine solution, a nano-titanium oxide suspension, a carbon nanotube and a graphene dispersion;
[0012] Step S3, preparing a core layer solution and a shell layer solution, wherein the mass percentages of the nano-silicon dioxide suspension, the polystyrene solution, and the chitin and chitosan mixed acetic acid solution in the core layer solution are 22%, 49%, and 29%, respectively, and the mass percentages of the nano-titanium oxide suspension, the polydopamine solution, and the carbon nanotube and graphene dispersion in the shell layer solution are 17%, 31%, and 52%, respectively;
[0013] Step S4, degassing the core layer solution and the shell layer solution;
[0014] Step S5, using the core layer solution and the shell layer solution to prepare a high-performance fiber polymer material;
[0015] Step S5 also includes the following steps:
[0016] Step S51: first, the core layer solution is injected into the inner layer spinneret of the spinning machine through a high-pressure pump, and the shell layer solution is injected into the outer layer spinneret of the spinning machine through a high-pressure pump. The core layer fibers are rapidly solidified after being ejected from the inner layer spinneret. When the core layer fibers are not completely solidified, the outer layer spinneret ejects the shell layer fibers outside the core layer fibers to form a high-performance fiber polymer material with a core layer structure.
[0017] Step S52: First, put the high-performance fiber polymer material with a core layer structure into a heat curing furnace, start the heat curing furnace after setting the heat curing temperature and time, and start the preliminary heat curing process. When the preliminary heat curing reaches the preset preliminary heat curing point, take the high-performance fiber polymer material with a core layer structure out of the heat curing furnace and quickly transfer it to a light curing device. After setting the light intensity and time of the light curing device, start the preliminary light curing process. When the preliminary light curing reaches the preset preliminary light curing point, perform heat curing and light curing alternately three times.
[0018] Preferably, step S1 further includes the following steps:
[0019] Step S11: when preparing the polystyrene solution, first grind the polystyrene into powder, slowly add it into the preheated organic solvent, and continuously stir it with a mechanical stirrer until the polystyrene is completely dissolved in the organic solvent to form a uniform polystyrene solution;
[0020] Step S12: when preparing the nano-silicon dioxide suspension, firstly prepare the raw materials, including silicon dioxide nano-powder, high-purity deionized water and surfactant, use an ultrasonic cleaner to ultrasonically clean the silicon dioxide nano-powder to remove impurities and organic matter on the surface, add the cleaned silicon dioxide nano-powder and surfactant into high-purity deionized water respectively, and mix them with an ultrasonic cleaner to form a mixed suspension, subject the mixed suspension to ultrasonic oscillation treatment to make the nanoparticles more fine and uniform, finally use a centrifuge to centrifuge the suspension to remove uneven substances, and put the nano-silicon dioxide suspension after centrifugation into a container;
[0021] Step S13: When preparing the chitosan and chitosan mixed acetic acid solution, grind the chitosan and chitosan into powders respectively, slowly add them into the acetic acid solution, and continuously stir with a mechanical stirrer until the chitosan and chitosan are completely dissolved in the acetic acid solution to form a uniform chitosan and chitosan mixed acetic acid solution.
[0022] Preferably, step S2 further includes the following steps:
[0023] Step S21: when preparing a polydopamine solution, first prepare the raw materials required for the preparation, including dopamine hydrochloride, tris(hydroxymethylaminomethane), hydrochloric acid, deionized water and sodium potassium ammonium persulfate, dissolve tris(hydroxymethylaminomethane) in deionized water, add hydrochloric acid, use a magnetic stirrer to continuously stir the mixture, adjust the pH value to 8.5, and form a tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, then add an oxidant sodium potassium ammonium persulfate to the mixture, during the reaction, the color of the solution will gradually change from light pink to dark brown, and finally to black, to form a polydopamine solution, and after the reaction is completed, remove the unreacted raw materials and impurities by filtering;
[0024] Step S22: when preparing a carbon nanotube and graphene dispersion, slowly add the carbon nanotube and graphene into ethanol at a ratio of 5:3, perform preliminary stirring to make them preliminarily dispersed, add a cationic perfluoro surfactant and an anionic surfactant as dispersants, and place the preliminarily dispersed solution into an ultrasonic disperser for ultrasonic treatment to destroy the agglomeration between the carbon nanotube and the graphene, so as to form a carbon nanotube and graphene dispersion;
[0025] Step S23: When preparing the nano titanium oxide suspension, first prepare the raw materials, including titanium oxide nano powder, high-purity deionized water and surfactant, use an ultrasonic cleaner to ultrasonically clean the titanium oxide nano powder to remove impurities and organic matter on the surface, add the cleaned titanium oxide nano powder and surfactant into high-purity deionized water respectively, and mix them with an ultrasonic cleaner to form a mixed suspension, and subject the mixed suspension to ultrasonic oscillation treatment to make the nano particles more fine and uniform, and finally use a centrifuge to centrifuge the suspension to remove uneven substances, and put the nano titanium oxide suspension after centrifugation into a container.
[0026] Preferably, step S3 further includes the following steps:
[0027] Step S31: When preparing the core layer solution, first pre-mix the nano-silica suspension with the polystyrene solution, use a mechanical stirrer to stir until the two are initially mixed and evenly mixed, slowly add the chitin and chitosan mixed acetic acid solution and continue stirring, and after the stirring is completed, put the mixed solution into an ultrasonic disperser for ultrasonic treatment to form a uniformly mixed core layer solution, and then use a filter to filter out the undispersed particles and impurities in the core layer solution.
[0028] Preferably, step S3 further includes the following steps:
[0029] Step S32: When preparing the shell solution, first pre-mix the nano-titanium oxide suspension and the polydopamine solution, use a mechanical stirrer to stir until the two are initially mixed evenly, slowly add the carbon nanotube and graphene dispersions and continue stirring, and after stirring, place them in an ultrasonic disperser for ultrasonic treatment to form a uniformly mixed shell solution, and then use a filter to filter out the undispersed particles and impurities in the shell solution.
[0030] Preferably, step S4 further includes the following steps:
[0031] Step S41: firstly, the core layer solution and the shell layer solution are subjected to initial vacuum degassing. Firstly, the uniformly mixed core layer solution and the shell layer solution are poured into the container of the vacuum degassing machine in sequence, the vacuum pump is turned on, and the pressure in the container is gradually reduced. The bubbles in the core layer solution and the shell layer solution are observed to gradually rise and be discharged. After maintaining the vacuum for a period of time, the vacuum pump is turned off, and the pressure is gradually released. The core layer solution and the shell layer solution are taken out, and it is observed whether there are bubbles gathered on the surface and bottom of the core layer solution and the shell layer solution. If there are bubbles gathered, the initial vacuum degassing is performed again until there is no obvious bubble gathering on the surface and bottom of the taken out core layer solution and the shell layer solution;
[0032] Step S42: Then, the core layer solution and the shell layer solution are subjected to secondary ultrasonic degassing. First, the core layer solution and the shell layer solution that have undergone the initial vacuum degassing are placed in the container of the ultrasonic degassing machine, and the frequency, power and degassing time of the ultrasonic wave are set. The ultrasonic degassing machine is turned on, and the bubbles in the solution are observed to gradually decrease under the action of the ultrasonic wave. After the set degassing time is reached, the ultrasonic degassing machine is turned off, and the core layer solution and the shell layer solution are taken out. It is observed whether there are bubbles gathered on the surface and bottom of the core layer solution and the shell layer solution. If there are bubbles gathered, secondary ultrasonic degassing is performed again until there is no obvious bubble gathering on the surface and bottom of the taken out core layer solution and the shell layer solution.
[0033] Preferably, the spinning preparation method of the high-performance fiber polymer material further comprises the following steps:
[0034] Step S6, washing and drying the high-performance fiber polymer material;
[0035] Step S7: performing a tensile property test on the prepared high-performance fiber polymer.
[0036] Preferably, step S6 further includes the following steps:
[0037] Step S61: When cleaning the high-performance fiber polymer material, the high-performance fiber polymer material is placed in a washing container, a washing liquid that covers the high-performance fiber polymer material is added, and the washing liquid is slowly stirred with a mechanical stirrer to make the high-performance fiber polymer material evenly distributed in the washing liquid, and the impurity particles on the surface of the high-performance fiber polymer material are removed. The washing liquid is replaced every 15 minutes until the washing liquid does not become turbid after stirring, and then the high-performance fiber polymer material is rinsed with deionized water to remove the residual washing solution and impurity particles, and the deionized water for rinsing is replaced multiple times until the deionized water for rinsing does not become turbid;
[0038] Step S62: when drying the high-performance fiber polymer material, evenly place the cleaned high-performance fiber polymer material on a tray of a drying device, weigh the weight of the high-performance fiber polymer material before drying, avoid overlapping and contacting the high-performance fiber polymer materials close to each other, place the tray in the drying device, set the temperature and time, and start the drying device;
[0039] Step S63: Check the dryness of the high-performance fiber polymer material every 1 hour, weigh the weight of the high-performance fiber polymer material each time it is dried, and record the weight, interval time, drying temperature, drying time and ventilation volume of each weighing. When the difference between the weights of the two weighings is 1.5%-5%, lower the drying temperature, shorten the drying time, and continue drying the high-performance fiber polymer material until the weights of the two weighings do not exceed 0.5%. Then turn off the drying equipment and take out the high-performance fiber polymer material.
[0040] Preferably, step S7 further includes the following steps:
[0041] Step S71: when performing a tensile property test on the high-performance fiber polymer material, 10 samples are randomly sampled from the prepared high-performance fiber polymer material, each sample is 200 mm long, the original cross-sectional area of each sample is measured and recorded, the sample is mounted in the fixture of the tensile testing machine, the fixture is adjusted to fix the sample, it is ensured that the sample does not slip or rotate during the test, and the sample axis is consistent with the stretching direction, the tensile testing machine is started after the stretching speed and test temperature are set, and a tensile load is applied to the sample at the set speed;
[0042] Step S72: When the sample reaches its maximum load-bearing capacity, it will break. At this time, the tensile testing machine will automatically stop, record the maximum tensile force when the sample breaks, measure and record the elongation of the sample, and calculate the tensile strength of the sample based on the original cross-sectional area and breaking force of the sample. Tensile strength = breaking force / original cross-sectional area.
[0043] Preferably, a high-performance fiber polymer material is a high-performance fiber polymer material obtained by the spinning preparation method of a high-performance fiber polymer material according to any one of claims 1-9.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. The present invention prepares a fiber polymer material with a core layer structure, and alternately performs thermal curing and photocuring on the prepared fiber polymer material. By preparing the fiber polymer material with a core layer structure, the internal structure of the fiber can be effectively regulated to make it have higher tensile strength and modulus. The design of this structure can enhance the mechanical properties of the fiber. At the same time, the fiber polymer material with a core layer structure may show better spinnability and stretchability during the spinning process, which helps to reduce production costs and improve production efficiency. In addition, thermal curing can enhance the internal cross-linking structure of the fiber and improve its stability and heat resistance, while photocuring can further cure the fiber surface and improve its wear resistance and weather resistance. The alternating curing process can make full use of the advantages of the two curing methods, so that the fiber shows better stability and controllability in the subsequent processing process. Therefore, it can solve the problem of how to optimize the processing performance of the fiber polymer material and improve the mechanical properties of the fiber polymer material.
[0046] 2. The present invention prepares a core layer solution containing nano-silicon dioxide, chitosan and chitosan, and prepares a shell layer solution containing nano-titanium oxide, nanotubes and graphene. Nano-silicon dioxide, nano-titanium oxide, nanotubes and graphene all have excellent thermal stability. Their addition can effectively improve the heat resistance of the fiber polymer material. Chitosan, chitosan, nano-titanium oxide and graphene all have good chemical stability, which can enhance the resistance of the fiber polymer material to chemical corrosion. By improving the heat resistance and chemical corrosion resistance, the fiber polymer material can be used in more extreme environments, including high temperature, high humidity, strong acid and strong alkali environments, greatly broadening the application scope of the fiber polymer material in the fields of aerospace, automobile, electronics and chemical industry. Therefore, it can solve the problem of how to improve the heat resistance and chemical corrosion resistance of the fiber polymer material, thereby broadening the application field of the fiber polymer material.
[0047] 3. The present invention uses ultrasonic and centrifugal technology when preparing the core layer solution and the shell layer solution, and combines a mechanical stirrer, an ultrasonic disperser, an ultrasonic cleaner and a centrifuge. When preparing the core layer solution and the shell layer solution, first use a mechanical stirrer to evenly mix the raw materials and the solvent, use an ultrasonic disperser to evenly disperse nano-silicon dioxide, carbon nanotubes and nano-titanium oxide into the solution to ensure the uniform distribution of the nanoparticles, use an ultrasonic cleaner to remove impurities on the surface of the raw materials, and at the same time, use a centrifuge to centrifuge the solution to remove large particle impurities and agglomerated nanoparticles to obtain pure and stable core layer solutions and shell layer solutions. The core layer solutions and shell layer solutions prepared by this method will have higher purity and stability, and the distribution of nano-silicon dioxide, carbon nanotubes and nano-titanium oxide inside them will be more uniform, thereby improving the mechanical properties and durability of the materials. Therefore, the problem of how to mix the raw materials evenly, improve the purity of the core layer solution and the shell layer solution and the quality of the prepared fiber polymer material can be solved.
[0048] 4. The present invention repeatedly performs primary vacuum degassing and secondary ultrasonic degassing on the core layer solution and the shell layer solution. Bubbles are likely to appear when preparing the core layer solution and the shell layer solution containing nanomaterials. The bubbles will cause the formation of voids and defects in the fiber polymer material, thereby reducing its mechanical properties and durability. In the process of preparing the core layer solution and the shell layer solution, the present invention first performs primary vacuum degassing. Under a vacuum environment, the bubbles in the solution will rapidly expand and burst due to the reduction of external pressure, effectively removing most of the bubbles in the solution. Then, the vacuum degassed solution is subjected to secondary ultrasonic degassing. Under the action of ultrasonic waves, the bubbles in the solution will continue to vibrate until they finally burst and dissipate. The strong vibration of ultrasonic waves can destroy the surface tension of the bubbles, making them easier to burst. This method can further remove small bubbles that may remain after the primary vacuum degassing. Repeating these two steps can ensure that the bubbles in the solution are removed as much as possible, thereby improving the stability and purity of the solution. Therefore, it can solve the problem of how to avoid the presence of bubbles in the preparation process, which leads to the formation of voids and defects in the fiber polymer material and reduces the mechanical properties and durability of the fiber polymer material. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Embodiment 1:
[0051] A spinning preparation method for a high-performance fiber polymer material, the spinning preparation method for the high-performance fiber polymer material is as follows:
[0052] Step S1, preparing a polystyrene solution, a nano-silicon dioxide suspension, and a chitin and chitosan mixed acetic acid solution;
[0053] Step S1 also includes the following steps:
[0054] Step S11: when preparing the polystyrene solution, first grind the polystyrene into powder, slowly add it into the preheated organic solvent, and continuously stir it with a mechanical stirrer until the polystyrene is completely dissolved in the organic solvent to form a uniform polystyrene solution;
[0055] Step S12: when preparing the nano-silicon dioxide suspension, firstly prepare the raw materials, including silicon dioxide nano-powder, high-purity deionized water and surfactant, use an ultrasonic cleaner to ultrasonically clean the silicon dioxide nano-powder to remove impurities and organic matter on the surface, add the cleaned silicon dioxide nano-powder and surfactant into high-purity deionized water respectively, and mix them with an ultrasonic cleaner to form a mixed suspension, subject the mixed suspension to ultrasonic oscillation treatment to make the nanoparticles more fine and uniform, finally use a centrifuge to centrifuge the suspension to remove uneven substances, and put the nano-silicon dioxide suspension after centrifugation into a container;
[0056] Step S13: When preparing the chitosan and chitosan mixed acetic acid solution, grind the chitosan and chitosan into powders respectively, slowly add them into the acetic acid solution, and continuously stir with a mechanical stirrer until the chitosan and chitosan are completely dissolved in the acetic acid solution to form a uniform chitosan and chitosan mixed acetic acid solution.
[0057] Furthermore, when preparing the polystyrene solution, the polystyrene is ground into powder to help increase the contact area between the polystyrene and the solvent, thereby accelerating the dissolution process, and the powdered polystyrene is slowly added to the preheated organic solvent. The preheated organic solvent can increase the dissolution rate and solubility. A mechanical stirrer is used to continuously stir to ensure that the polystyrene powder is evenly dispersed in the organic solvent and promote dissolution. The stirring is continued until the polystyrene is completely dissolved in the organic solvent to form a uniform polystyrene solution.
[0058] When preparing the nano-silicon dioxide suspension, prepare silicon dioxide nano-powder, high-purity deionized water and a surfactant, use an ultrasonic cleaner to clean the silicon dioxide nano-powder to remove impurities and organic matter on the surface and ensure the purity of the nano-powder, add the cleaned silicon dioxide nano-powder and the surfactant into the high-purity deionized water, use an ultrasonic cleaner to mix them to form a preliminary mixed suspension, then perform ultrasonic oscillation on the mixed suspension to make the nano-particles finer and more uniform, improve the stability and uniformity of the suspension, use a centrifuge to centrifuge the suspension to remove uneven or agglomerated substances and improve the quality of the suspension, and finally put the nano-silicon dioxide suspension after centrifugation into a container for standby use;
[0059] When preparing chitin and chitosan acetic acid solutions, chitin and chitosan are ground into powder to increase the contact area with the acetic acid solution and accelerate dissolution. The powdered chitin and chitosan are slowly added to the acetic acid solution, and a mechanical stirrer is used to continuously stir to ensure that the chitin and chitosan powders are evenly dispersed in the acetic acid solution and to promote dissolution. The stirring is continued until the chitin and chitosan are completely dissolved in the acetic acid solution to form a uniform chitin and chitosan acetic acid solution.
[0060] Embodiment 2:
[0061] A spinning preparation method for a high-performance fiber polymer material, the spinning preparation method for the high-performance fiber polymer material is as follows:
[0062] Step S2, preparing a polydopamine solution, a nano-titanium oxide suspension, a carbon nanotube and a graphene dispersion;
[0063] Step S2 also includes the following steps:
[0064] Step S21: when preparing a polydopamine solution, first prepare the raw materials required for the preparation, including dopamine hydrochloride, tris(hydroxymethylaminomethane), hydrochloric acid, deionized water and sodium potassium ammonium persulfate, dissolve tris(hydroxymethylaminomethane) in deionized water, add hydrochloric acid, use a magnetic stirrer to continuously stir the mixture, adjust the pH value to 8.5, and form a tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, then add an oxidant sodium potassium ammonium persulfate to the mixture, during the reaction, the color of the solution will gradually change from light pink to dark brown, and finally to black, to form a polydopamine solution, and after the reaction is completed, remove the unreacted raw materials and impurities by filtering;
[0065] Step S22: when preparing a carbon nanotube and graphene dispersion, slowly add the carbon nanotube and graphene into ethanol at a ratio of 5:3, perform preliminary stirring to make them preliminarily dispersed, add a cationic perfluoro surfactant and an anionic surfactant as dispersants, and place the preliminarily dispersed solution into an ultrasonic disperser for ultrasonic treatment to destroy the agglomeration between the carbon nanotube and the graphene, so as to form a carbon nanotube and graphene dispersion;
[0066] Step S23: When preparing the nano titanium oxide suspension, first prepare the raw materials, including titanium oxide nano powder, high-purity deionized water and surfactant, use an ultrasonic cleaner to ultrasonically clean the titanium oxide nano powder to remove impurities and organic matter on the surface, add the cleaned titanium oxide nano powder and surfactant into high-purity deionized water respectively, and mix them with an ultrasonic cleaner to form a mixed suspension, and subject the mixed suspension to ultrasonic oscillation treatment to make the nano particles more fine and uniform, and finally use a centrifuge to centrifuge the suspension to remove uneven substances, and put the nano titanium oxide suspension after centrifugation into a container.
[0067] Further, when preparing the polydopamine solution, dopamine hydrochloride, tris(hydroxymethylaminomethane), hydrochloric acid, deionized water and sodium potassium ammonium persulfate are prepared, tris(hydroxymethylaminomethane) is dissolved in deionized water, hydrochloric acid is added, and the mixture is continuously stirred using a magnetic stirrer, and the pH value is adjusted to 8.5 to form a tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, which provides a suitable pH environment for the polymerization of polydopamine, and then an oxidant sodium potassium ammonium persulfate is added to the mixture to start an oxidative polymerization reaction. During the reaction, the color of the solution changes from light pink to dark brown and finally to black. This is because dopamine undergoes a polymerization reaction under the action of the oxidant to form polydopamine. After the reaction is completed, unreacted raw materials and impurities are removed by filtration to obtain a pure polydopamine solution;
[0068] When preparing a carbon nanotube and graphene dispersion, the carbon nanotube and graphene are slowly added to ethanol in a ratio of 5:3, and are initially stirred to be initially dispersed, and a cationic perfluoro surfactant and an anionic surfactant are added as dispersants, wherein the dispersants are helpful in destroying the agglomeration between the carbon nanotube and the graphene, so that the carbon nanotube and the graphene are better dispersed in the ethanol, and the initially dispersed solution is placed in an ultrasonic disperser for ultrasonic treatment, wherein the vibration of the ultrasonic wave can further destroy the agglomeration between the carbon nanotube and the graphene, so as to form a stable dispersion;
[0069] When preparing the nano titanium oxide suspension, titanium oxide nano powder, high-purity deionized water and surfactant are prepared, and the titanium oxide nano powder is ultrasonically cleaned by using an ultrasonic cleaner to remove impurities and organic matter on the surface to ensure the purity of the nano powder. The cleaned titanium oxide nano powder and surfactant are respectively added to high-purity deionized water and mixed by using an ultrasonic cleaner to form a mixed suspension. The mixed suspension is then subjected to ultrasonic oscillation treatment to make the nano particles finer and more uniform. The suspension is centrifuged by using a centrifuge to remove uneven substances to obtain a purer and more uniform nano titanium oxide suspension. Finally, the nano titanium oxide suspension after centrifugation is placed in a container for standby use.
[0070] Embodiment three:
[0071] A spinning preparation method for a high-performance fiber polymer material, the spinning preparation method for the high-performance fiber polymer material is as follows:
[0072] Step S3, preparing a core layer solution and a shell layer solution, wherein the mass percentages of the nano-silicon dioxide suspension, the polystyrene solution, and the chitin and chitosan mixed acetic acid solution in the core layer solution are 22%, 49%, and 29%, respectively, and the mass percentages of the nano-titanium oxide suspension, the polydopamine solution, and the carbon nanotube and graphene dispersion in the shell layer solution are 17%, 31%, and 52%, respectively;
[0073] Step S3 also includes the following steps:
[0074] Step S31: When preparing the core layer solution, first pre-mix the nano-silica suspension with the polystyrene solution, use a mechanical stirrer to stir until the two are initially mixed and evenly mixed, slowly add the chitin and chitosan mixed acetic acid solution and continue stirring, and after the stirring is completed, put the mixed solution into an ultrasonic disperser for ultrasonic treatment to form a uniformly mixed core layer solution, and then use a filter to filter out the undispersed particles and impurities in the core layer solution.
[0075] Furthermore, the mechanical stirrer can preliminarily mix the nano-silica suspension and the polystyrene solution uniformly, but the nano-silica is prone to agglomeration. The subsequent ultrasonic treatment can further destroy these agglomerates, so that the nano-silica, polystyrene, chitin and chitosan are more evenly dispersed in the solution. The uniform dispersion state can ensure the stability of the solution and prevent precipitation or stratification during long-term storage or use, which is conducive to the preparation of high-performance fiber polymer materials.
[0076] Nano-silicon dioxide has excellent mechanical properties, thermal stability and chemical stability, polystyrene is a commonly used polymer material, and chitin and chitosan are biocompatible and biodegradable. Mixing these materials together can form a core layer material of a high-performance fiber polymer material with multiple functionalities. The uniform mixing state can ensure that these materials are evenly distributed in the core layer, so as to give full play to their respective advantages and improve the overall performance of the core layer material of the high-performance fiber polymer material. The filtration step can remove undispersed particles and impurities in the mixed solution, ensure the purity of the core layer solution, and avoid impurities affecting the performance or stability of the high-performance fiber polymer material.
[0077] Embodiment 4:
[0078] A spinning preparation method for a high-performance fiber polymer material, the spinning preparation method for the high-performance fiber polymer material is as follows:
[0079] Step S3, preparing a core layer solution and a shell layer solution, wherein the mass percentages of the nano-silicon dioxide suspension, the polystyrene solution, and the chitin and chitosan mixed acetic acid solution in the core layer solution are 22%, 49%, and 29%, respectively, and the mass percentages of the nano-titanium oxide suspension, the polydopamine solution, and the carbon nanotube and graphene dispersion in the shell layer solution are 17%, 31%, and 52%, respectively;
[0080] Step S3 also includes the following steps:
[0081] Step S32: When preparing the shell solution, first pre-mix the nano-titanium oxide suspension and the polydopamine solution, use a mechanical stirrer to stir until the two are initially mixed evenly, slowly add the carbon nanotube and graphene dispersions and continue stirring, and after stirring, place them in an ultrasonic disperser for ultrasonic treatment to form a uniformly mixed shell solution, and then use a filter to filter out the undispersed particles and impurities in the shell solution.
[0082] Furthermore, the mechanical stirrer can make the nano-titanium oxide suspension and the polydopamine solution preliminarily mixed and uniform, but the nano-titanium oxide is easy to agglomerate. The subsequent ultrasonic treatment can further destroy the agglomerates, so that the nano-titanium oxide, polydopamine, carbon nanotubes and graphene are more evenly dispersed in the solution. The uniform dispersion state can ensure the stability of the solution and prevent precipitation or stratification during long-term storage or use, which is conducive to the preparation of high-performance fiber polymer materials.
[0083] Nano-titanium oxide has excellent photocatalytic and UV resistance properties, polydopamine has biocompatibility and adhesion, carbon nanotubes and graphene have excellent conductivity and mechanical properties. Mixing these materials together can form a shell structure of high-performance fiber polymer materials with multiple functionalities. The uniform mixing state can ensure that these materials are evenly distributed in the shell, so as to give full play to their respective advantages and improve the overall performance of the shell material. At the same time, the filtration step can remove undispersed particles and impurities in the mixed solution, ensure the purity of the shell solution, and avoid impurities that affect the performance of the high-performance fiber polymer material.
[0084] Embodiment five:
[0085] A spinning preparation method for a high-performance fiber polymer material, the spinning preparation method for the high-performance fiber polymer material is as follows:
[0086] Step S4, degassing the core layer solution and the shell layer solution;
[0087] Step S4 also includes the following steps:
[0088] Step S41: firstly, the core layer solution and the shell layer solution are subjected to initial vacuum degassing. Firstly, the uniformly mixed core layer solution and the shell layer solution are poured into the container of the vacuum degassing machine in sequence, the vacuum pump is turned on, and the pressure in the container is gradually reduced. The bubbles in the core layer solution and the shell layer solution are observed to gradually rise and be discharged. After maintaining the vacuum for a period of time, the vacuum pump is turned off, and the pressure is gradually released. The core layer solution and the shell layer solution are taken out, and it is observed whether there are bubbles gathered on the surface and bottom of the core layer solution and the shell layer solution. If there are bubbles gathered, the initial vacuum degassing is performed again until there is no obvious bubble gathering on the surface and bottom of the taken out core layer solution and the shell layer solution;
[0089] Step S42: Then, the core layer solution and the shell layer solution are subjected to secondary ultrasonic degassing. First, the core layer solution and the shell layer solution that have undergone the initial vacuum degassing are placed in the container of the ultrasonic degassing machine, and the frequency, power and degassing time of the ultrasonic wave are set. The ultrasonic degassing machine is turned on, and the bubbles in the solution are observed to gradually decrease under the action of the ultrasonic wave. After the set degassing time is reached, the ultrasonic degassing machine is turned off, and the core layer solution and the shell layer solution are taken out. It is observed whether there are bubbles gathered on the surface and bottom of the core layer solution and the shell layer solution. If there are bubbles gathered, secondary ultrasonic degassing is performed again until there is no obvious bubble gathering on the surface and bottom of the taken out core layer solution and the shell layer solution.
[0090] Furthermore, during the preparation process, air will be mixed into the core layer solution and the shell layer solution to form bubbles. If these bubbles are not removed, they may affect the quality and performance of the fiber polymer material finally prepared. Vacuum degassing can effectively remove these bubbles and ensure the homogeneity of the solution, thereby improving the quality and performance of the fiber. Through effective vacuum degassing, the defective rate caused by bubbles can be reduced, thereby saving raw materials and production costs.
[0091] Although most of the bubbles can be removed after the initial vacuum degassing, there are still tiny bubbles remaining. Ultrasonic degassing can break these tiny bubbles and ensure the purity of the solution. Ultrasonic degassing can further improve the quality of the solution and ensure that no defects will be caused by bubbles in the subsequent spinning and curing processes. By completely removing bubbles, the uniformity and stability of the spinning process can be optimized, thereby improving the quality and performance of the fiber. A solution without bubbles can react more evenly during curing and cross-linking, which helps to enhance the mechanical properties and structural integrity of the final product. By repeating the process, if bubbles are still observed to gather on the surface and bottom of the solution, it is necessary to repeat the initial vacuum degassing and the secondary ultrasonic degassing until there are no obvious bubbles in the solution, which can effectively ensure the quality of the core layer solution and the shell layer solution.
[0092] Embodiment six:
[0093] A spinning preparation method for a high-performance fiber polymer material, the spinning preparation method for the high-performance fiber polymer material is as follows:
[0094] Step S5 also includes the following steps:
[0095] Step S51: first, the core layer solution is injected into the inner layer spinneret of the spinning machine through a high-pressure pump, and the shell layer solution is injected into the outer layer spinneret of the spinning machine through a high-pressure pump. The core layer fibers are rapidly solidified after being ejected from the inner layer spinneret. When the core layer fibers are not completely solidified, the outer layer spinneret ejects the shell layer fibers outside the core layer fibers to form a high-performance fiber polymer material with a core layer structure.
[0096] Step S52: First, put the high-performance fiber polymer material with a core layer structure into a heat curing furnace, start the heat curing furnace after setting the heat curing temperature and time, and start the preliminary heat curing process. When the preliminary heat curing reaches the preset preliminary heat curing point, take the high-performance fiber polymer material with a core layer structure out of the heat curing furnace and quickly transfer it to a light curing device. After setting the light intensity and time of the light curing device, start the preliminary light curing process. When the preliminary light curing reaches the preset preliminary light curing point, perform heat curing and light curing alternately three times.
[0097] Furthermore, a high-pressure pump is first used to inject the core layer solution into the inner spinneret of the spinning machine, and at the same time, the shell layer solution is injected into the outer spinneret of the spinning machine. When the high-pressure pump starts to work, the core layer fibers are ejected from the inner spinneret, and the core layer fibers will quickly begin to solidify after being ejected. When the core layer fibers have not yet completely solidified, the outer spinneret ejects the shell layer fibers outside the core layer fibers, and the shell layer fibers will be wrapped outside the core layer fibers, forming a high-performance fiber polymer material with a core layer structure;
[0098] Putting a high-performance fiber polymer material with a core layer structure into a heat curing furnace, starting the heat curing furnace after setting the heat curing temperature and time, and starting a preliminary heat curing process. Heat curing causes the polymer chain segments in the fiber to undergo a certain degree of cross-linking reaction by heating to form an initial cured structure. When the preliminary heat curing reaches a preset preliminary heat curing point, the fiber polymer material is quickly taken out of the heat curing furnace and transferred to a light curing device. In the light curing device, after setting the light intensity and time, a preliminary light curing process is started. Light curing uses light of a specific wavelength to trigger a cross-linking reaction of the polymer in the fiber polymer material, thereby further strengthening the cured structure of the fiber polymer material.
[0099] When the initial light curing reaches the preset initial light curing point, thermal curing and light curing will be started alternately. This alternating curing process will be repeated three times. Thermal curing and light curing each have their own characteristics and advantages. Thermal curing usually causes chemical reactions between polymer segments by heating, while light curing triggers cross-linking reactions of polymers by light of a specific wavelength. By alternating these two curing methods, it can be ensured that all parts of the fiber can be uniformly cured to avoid partial uncured or incompletely cured conditions.
[0100] Through the process of alternating curing, the cross-linking density inside the fiber polymer material will increase, thereby improving the stability and durability of the fiber polymer material. This stable structure enables the fiber polymer material to maintain its shape and performance stability when facing external stress and environmental changes, thereby extending its service life. At the same time, during the curing process, the fiber polymer material will shrink or deform due to the release of internal stress. Through alternating curing, these internal stresses can be gradually released, and the shrinkage and deformation of the fiber polymer material can be controlled, thereby obtaining a more uniform and straight fiber polymer material.
[0101] Embodiment seven:
[0102] A spinning method for preparing a high-performance fiber polymer material, the spinning method for preparing a high-performance fiber polymer material also includes the following steps:
[0103] Step S6, washing and drying the high-performance fiber polymer material;
[0104] Step S6 also includes the following steps:
[0105] Step S61: When cleaning the high-performance fiber polymer material, the high-performance fiber polymer material is placed in a washing container, a washing liquid that covers the high-performance fiber polymer material is added, and the washing liquid is slowly stirred with a mechanical stirrer to make the high-performance fiber polymer material evenly distributed in the washing liquid, and the impurity particles on the surface of the high-performance fiber polymer material are removed. The washing liquid is replaced every 15 minutes until the washing liquid does not become turbid after stirring, and then the high-performance fiber polymer material is rinsed with deionized water to remove the residual washing solution and impurity particles, and the deionized water for rinsing is replaced multiple times until the deionized water for rinsing does not become turbid;
[0106] Step S62: when drying the high-performance fiber polymer material, evenly place the cleaned high-performance fiber polymer material on a tray of a drying device, weigh the weight of the high-performance fiber polymer material before drying, avoid overlapping and contacting the high-performance fiber polymer materials close to each other, place the tray in the drying device, set the temperature and time, and start the drying device;
[0107] Step S63: Check the dryness of the high-performance fiber polymer material every 1 hour, weigh the weight of the high-performance fiber polymer material each time it is dried, and record the weight, interval time, drying temperature, drying time and ventilation volume of each weighing. When the difference between the weights of the two weighings is 1.5%-5%, lower the drying temperature, shorten the drying time, and continue drying the high-performance fiber polymer material until the weights of the two weighings do not exceed 0.5%. Then turn off the drying equipment and take out the high-performance fiber polymer material.
[0108] Furthermore, the use of washing liquid can effectively dissolve and remove impurity particles on the surface of the fiber, ensuring the purity and quality of the fiber. The washing liquid can be slowly stirred by a mechanical stirrer to evenly distribute the fibers in the washing liquid, which helps to improve the cleaning efficiency and ensure that each fiber can be exposed to fresh washing liquid. The washing liquid is replaced every 15 minutes to prevent the saturated washing liquid from contaminating the fiber again, ensuring the continuity and effectiveness of the cleaning process. By observing whether the washing liquid becomes turbid after stirring, it can be judged whether the fiber has been cleaned. If the washing liquid does not become turbid, it means that the impurities on the surface of the fiber have been removed. The use of deionized water for rinsing is to remove the residual washing solution and impurity particles to avoid these substances from having adverse effects on the performance of the fiber. The deionized water for rinsing is replaced several times until the rinsing water does not become turbid to ensure that all residual detergents and impurities are completely removed.
[0109] By drying, the moisture and other volatile substances that may be adsorbed during the cleaning process can be completely removed from the fiber. If these substances are not removed, the quality and performance of the fiber will be affected. The weight of the high-performance fiber polymer material is weighed before drying. This is to record the weight change before and after drying, so that the amount of moisture and volatile substances removed during the drying process can be calculated. The high-performance fiber polymer material is evenly placed on the tray of the drying equipment and avoids overlapping and contact. This is to ensure that each fiber can be evenly exposed to hot air, thereby improving the drying efficiency and effect. According to the characteristics of the fiber material and the drying requirements, the appropriate temperature and time are set to ensure that the drying process can effectively remove moisture without damaging the fiber due to excessive temperature. The tray is placed in the drying equipment and the equipment is started to start the drying process, which helps to achieve uniform drying of the fiber. The dried fiber polymer material will have better storage stability and service life, because drying can reduce the chance of microbial growth and prevent mildew and other problems caused by humidity;
[0110] Weighing the high-performance fiber polymer material every hour can help monitor the drying progress and ensure that the fiber material gradually approaches the ideal drying state. Recording the weight, interval time, drying temperature, drying time and ventilation volume of each weighing is very important for analyzing the efficiency of the drying process and optimizing the drying parameters. When the weight of the two weighings differs by 1.5%-5%, it means that the drying rate is fast and the drying temperature needs to be lowered or the drying time needs to be shortened to avoid fiber damage or energy waste caused by excessive drying. Continue drying until the weight of the two weighings does not exceed 0.5%. This is to ensure that the fiber material is evenly and thoroughly dried, thereby ensuring its performance and quality. By precisely controlling the degree of drying, unnecessary energy consumption can be avoided and the energy efficiency of the drying process can be improved. Excessive drying can lead to a decrease in the performance of the fiber material, such as reduced strength and increased brittleness, so it is crucial to control the degree of drying.
[0111] Embodiment eight:
[0112] A spinning method for preparing a high-performance fiber polymer material, the spinning method for preparing a high-performance fiber polymer material also includes the following steps:
[0113] Step S7: performing a tensile property test on the prepared high-performance fiber polymer.
[0114] Step S7 also includes the following steps:
[0115] Step S71: when performing a tensile property test on the high-performance fiber polymer material, 10 samples are randomly sampled from the prepared high-performance fiber polymer material, each sample is 200 mm long, the original cross-sectional area of each sample is measured and recorded, the sample is mounted in the fixture of the tensile testing machine, the fixture is adjusted to fix the sample, it is ensured that the sample does not slip or rotate during the test, and the sample axis is consistent with the stretching direction, the tensile testing machine is started after the stretching speed and test temperature are set, and a tensile load is applied to the sample at the set speed;
[0116] Step S72: When the sample reaches its maximum load-bearing capacity, it will break. At this time, the tensile testing machine will automatically stop, record the maximum tensile force when the sample breaks, measure and record the elongation of the sample, and calculate the tensile strength of the sample based on the original cross-sectional area and breaking force of the sample. Tensile strength = breaking force / original cross-sectional area.
[0117] Further, the tensile properties test results are as follows:
[0118]
[0119]
[0120] The tensile properties test results show that the prepared high-performance fiber polymer material has good tensile properties.
[0121] Furthermore, a high-performance fiber polymer material is provided, which is obtained by the spinning preparation method of a high-performance fiber polymer material according to any one of claims 1-9.
[0122] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A spinning method for preparing a high-performance fiber polymer material, characterized in that: The spinning preparation method of the high-performance fiber polymer material is as follows: Step S1, preparing a polystyrene solution, a nano-silicon dioxide suspension, and a chitin and chitosan mixed acetic acid solution; Step S2, preparing a polydopamine solution, a nano-titanium oxide suspension, a carbon nanotube and a graphene dispersion; Step S3, preparing a core layer solution and a shell layer solution, wherein the mass percentages of the nano-silicon dioxide suspension, the polystyrene solution, and the chitin and chitosan mixed acetic acid solution in the core layer solution are 22%, 49%, and 29%, respectively, and the mass percentages of the nano-titanium oxide suspension, the polydopamine solution, and the carbon nanotube and graphene dispersion in the shell layer solution are 17%, 31%, and 52%, respectively; Step S4, degassing the core layer solution and the shell layer solution; Step S5, using the core layer solution and the shell layer solution to prepare a high-performance fiber polymer material; Step S5 also includes the following steps: Step S51: first, the core layer solution is injected into the inner layer spinneret of the spinning machine through a high-pressure pump, and the shell layer solution is injected into the outer layer spinneret of the spinning machine through a high-pressure pump. The core layer fibers are rapidly solidified after being ejected from the inner layer spinneret. When the core layer fibers are not completely solidified, the outer layer spinneret ejects the shell layer fibers outside the core layer fibers to form a high-performance fiber polymer material with a core layer structure. Step S52: First, put the high-performance fiber polymer material with a core layer structure into a heat curing furnace, start the heat curing furnace after setting the heat curing temperature and time, and start the preliminary heat curing process. When the preliminary heat curing reaches the preset preliminary heat curing point, take the high-performance fiber polymer material with a core layer structure out of the heat curing furnace and quickly transfer it to a light curing device. After setting the light intensity and time of the light curing device, start the preliminary light curing process. When the preliminary light curing reaches the preset preliminary light curing point, perform heat curing and light curing alternately three times.
2. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S1 also includes the following steps: Step S11: when preparing the polystyrene solution, first grind the polystyrene into powder, slowly add it into the preheated organic solvent, and continuously stir it with a mechanical stirrer until the polystyrene is completely dissolved in the organic solvent to form a uniform polystyrene solution; Step S12: when preparing the nano-silicon dioxide suspension, firstly prepare the raw materials, including silicon dioxide nano-powder, high-purity deionized water and surfactant, use an ultrasonic cleaner to ultrasonically clean the silicon dioxide nano-powder to remove impurities and organic matter on the surface, add the cleaned silicon dioxide nano-powder and surfactant into high-purity deionized water respectively, and mix them with an ultrasonic cleaner to form a mixed suspension, subject the mixed suspension to ultrasonic oscillation treatment to make the nanoparticles more fine and uniform, finally use a centrifuge to centrifuge the suspension to remove uneven substances, and put the nano-silicon dioxide suspension after centrifugation into a container; Step S13: When preparing the chitosan and chitosan mixed acetic acid solution, grind the chitosan and chitosan into powders respectively, slowly add them into the acetic acid solution, and continuously stir with a mechanical stirrer until the chitosan and chitosan are completely dissolved in the acetic acid solution to form a uniform chitosan and chitosan mixed acetic acid solution.
3. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S2 also includes the following steps: Step S21: when preparing a polydopamine solution, first prepare the raw materials required for the preparation, including dopamine hydrochloride, tris(hydroxymethylaminomethane), hydrochloric acid, deionized water and sodium potassium ammonium persulfate, dissolve tris(hydroxymethylaminomethane) in deionized water, add hydrochloric acid, use a magnetic stirrer to continuously stir the mixture, adjust the pH value to 8.5, and form a tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, then add an oxidant sodium potassium ammonium persulfate to the mixture, during the reaction, the color of the solution will gradually change from light pink to dark brown, and finally to black, to form a polydopamine solution, and after the reaction is completed, remove the unreacted raw materials and impurities by filtering; Step S22: when preparing a carbon nanotube and graphene dispersion, slowly add the carbon nanotube and graphene into ethanol at a ratio of 5:3, perform preliminary stirring to make them preliminarily dispersed, add a cationic perfluoro surfactant and an anionic surfactant as dispersants, and place the preliminarily dispersed solution into an ultrasonic disperser for ultrasonic treatment to destroy the agglomeration between the carbon nanotube and the graphene, so as to form a carbon nanotube and graphene dispersion; Step S23: When preparing the nano titanium oxide suspension, first prepare the raw materials, including titanium oxide nano powder, high-purity deionized water and surfactant, use an ultrasonic cleaner to ultrasonically clean the titanium oxide nano powder to remove impurities and organic matter on the surface, add the cleaned titanium oxide nano powder and surfactant into high-purity deionized water respectively, and mix them with an ultrasonic cleaner to form a mixed suspension, and subject the mixed suspension to ultrasonic oscillation treatment to make the nano particles more fine and uniform, and finally use a centrifuge to centrifuge the suspension to remove uneven substances, and put the nano titanium oxide suspension after centrifugation into a container.
4. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S3 also includes the following steps: Step S31: When preparing the core layer solution, first pre-mix the nano-silica suspension with the polystyrene solution, use a mechanical stirrer to stir until the two are initially mixed and evenly mixed, slowly add the chitin and chitosan mixed acetic acid solution and continue stirring, and after the stirring is completed, put the mixed solution into an ultrasonic disperser for ultrasonic treatment to form a uniformly mixed core layer solution, and then use a filter to filter out the undispersed particles and impurities in the core layer solution.
5. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S3 also includes the following steps: Step S32: When preparing the shell solution, first pre-mix the nano-titanium oxide suspension and the polydopamine solution, use a mechanical stirrer to stir until the two are initially mixed evenly, slowly add the carbon nanotube and graphene dispersions and continue stirring, and after stirring, place them in an ultrasonic disperser for ultrasonic treatment to form a uniformly mixed shell solution, and then use a filter to filter out the undispersed particles and impurities in the shell solution.
6. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S4 also includes the following steps: Step S41: firstly, the core layer solution and the shell layer solution are subjected to initial vacuum degassing. Firstly, the uniformly mixed core layer solution and the shell layer solution are poured into the container of the vacuum degassing machine in sequence, the vacuum pump is turned on, and the pressure in the container is gradually reduced. The bubbles in the core layer solution and the shell layer solution are observed to gradually rise and be discharged. After maintaining the vacuum for a period of time, the vacuum pump is turned off, and the pressure is gradually released. The core layer solution and the shell layer solution are taken out, and it is observed whether there are bubbles gathered on the surface and bottom of the core layer solution and the shell layer solution. If there are bubbles gathered, the initial vacuum degassing is performed again until there is no obvious bubble gathering on the surface and bottom of the taken out core layer solution and the shell layer solution; Step S42: Then, the core layer solution and the shell layer solution are subjected to secondary ultrasonic degassing. First, the core layer solution and the shell layer solution that have undergone the initial vacuum degassing are placed in the container of the ultrasonic degassing machine, and the frequency, power and degassing time of the ultrasonic wave are set. The ultrasonic degassing machine is turned on, and the bubbles in the solution are observed to gradually decrease under the action of the ultrasonic wave. After the set degassing time is reached, the ultrasonic degassing machine is turned off, and the core layer solution and the shell layer solution are taken out. It is observed whether there are bubbles gathered on the surface and bottom of the core layer solution and the shell layer solution. If there are bubbles gathered, secondary ultrasonic degassing is performed again until there is no obvious bubble gathering on the surface and bottom of the taken out core layer solution and the shell layer solution.
7. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: The spinning preparation method of the high-performance fiber polymer material also includes the following steps: Step S6, washing and drying the high-performance fiber polymer material; Step S7: performing a tensile property test on the prepared high-performance fiber polymer.
8. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S6 also includes the following steps: Step S61: When cleaning the high-performance fiber polymer material, the high-performance fiber polymer material is placed in a washing container, a washing liquid that covers the high-performance fiber polymer material is added, and the washing liquid is slowly stirred with a mechanical stirrer to make the high-performance fiber polymer material evenly distributed in the washing liquid, and the impurity particles on the surface of the high-performance fiber polymer material are removed. The washing liquid is replaced every 15 minutes until the washing liquid does not become turbid after stirring, and then the high-performance fiber polymer material is rinsed with deionized water to remove the residual washing solution and impurity particles, and the deionized water for rinsing is replaced multiple times until the deionized water for rinsing does not become turbid; Step S62: when drying the high-performance fiber polymer material, evenly place the cleaned high-performance fiber polymer material on a tray of a drying device, weigh the weight of the high-performance fiber polymer material before drying, avoid overlapping and contacting the high-performance fiber polymer materials close to each other, place the tray in the drying device, set the temperature and time, and start the drying device; Step S63: Check the dryness of the high-performance fiber polymer material every 1 hour, weigh the weight of the high-performance fiber polymer material each time it is dried, and record the weight, interval time, drying temperature, drying time and ventilation volume of each weighing. When the difference between the weights of the two weighings is 1.5%-5%, lower the drying temperature, shorten the drying time, and continue drying the high-performance fiber polymer material until the weights of the two weighings do not exceed 0.5%. Then turn off the drying equipment and take out the high-performance fiber polymer material.
9. The spinning method for preparing a high-performance fiber polymer material according to claim 1, characterized in that: Step S7 also includes the following steps: Step S71: when performing a tensile property test on the high-performance fiber polymer material, 10 samples are randomly sampled from the prepared high-performance fiber polymer material, each sample is 200 mm long, the original cross-sectional area of each sample is measured and recorded, the sample is mounted in the fixture of the tensile testing machine, the fixture is adjusted to fix the sample, it is ensured that the sample does not slip or rotate during the test, and the sample axis is consistent with the stretching direction, the tensile testing machine is started after the stretching speed and test temperature are set, and a tensile load is applied to the sample at the set speed; Step S72: When the sample reaches its maximum load-bearing capacity, it will break. At this time, the tensile testing machine will automatically stop, record the maximum tensile force when the sample breaks, measure and record the elongation of the sample, and calculate the tensile strength of the sample based on the original cross-sectional area and breaking force of the sample. Tensile strength = breaking force / original cross-sectional area.
10. A high performance fiber polymer material, characterized in that: A high-performance fiber polymer material obtained by the spinning preparation method of a high-performance fiber polymer material according to any one of claims 1-9.
Citation Information
Patent Citations
Core-shell structure fiber based on carbon nano material and preparation method thereof
CN107177892A
Chitin-chitosan nano composite fiber as well as preparation method and application thereof
CN111876851A
High-performance sole material and preparation method therefor
WO2023207316A1
